KEMAMPUAN BERBAHASA INGGRIS LISAN KARYAWAN FRONT OFFICE HOTEL JAVA HERITAGE - sani, Nabila Muthia; Agustina, Mia Fitria; Februansyah, Rizki (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2021)
The purpose of writing this article is to find out the standard of service in English and the ability of Java Heritage Hotel employees to speak English. Hotel Java Heritage is one of the 4-star hotels in Purwokerto. Hotel Java Heritage provides a variety of facilities and services provided for the satisfaction of guests staying at the hotel. This hotel is not only visited by domestic guests, but also visited by foreign guests. The use of English in the hotel environment is very important as a means of communication and good service to foreign guests. Hotel employees, especially the front office, use English as a medium to communicate with these guests. However, the different educational backgrounds of hotel front office employees make each employee have different English skills, especially in communicating using English. In communicating in English, front office employees face several obstacles, such as when a foreign guest speaks, the employee cannot understand the meaning because the guest speaks too fast and the lack of English vocabulary or vocabulary makes it difficult for employees to pronounce a word or sentence. Therefore, to improve employees' English skills, the hotel management can provide intensive English training or courses to employees